DISCOURSE ANALYSIS AND BUSINESS ENGLISH - Baramee Kheovichai (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This paper outlines possible contributions that discourse analysis can make to the study of business English. It first explains the differences between business English and casual conversation, resulting in the need for the linguistic description of business English. A model of business discourse analysis (Bhatia, 2004) is explained. Three example research strands ol business discourse analysis. including genre analysis, relational aspects ofinteraction and business Enelish used by non-native speakers, are explicated. Implications for language teaching are then discussed